Economic growth and sustainability reporting: The moderating role of intellectual capital and STEM CEO - Iman Harymawan; Fahriza Saputra (Journal of Innovation in Business and Economics, 2026)
This study investigates the impact of Gross Domestic Product (GDP) per capita on sustainability reporting (CSRD), moderated by Intellectual Capital (VAIC) and CEOs with STEM backgrounds (STEMCEO). The sample consists of 364 observations from 211 Asian companies covering the period from 2021 to 2022. Regression analysis using Moderated Regression Analysis (MRA) indicates a significant positive effect of GDP on CSRD. The moderating role of intellectual capital weakens the relationship between GDP and CSRD, while the moderating effect of STEM CEOs is insignificant. Analysis of the control variables reveals that firm age (FAGE) positively affects CSRD. Additionally, the influence of GDP and VAIC on CSRD is more pronounced in younger companies. This study provides valuable insights into the interplay between GDP per capita, intellectual capital, and sustainability reporting for academics and corporate management.